Hybrid sonochemic urea-nitrate combustion preparation of CuO/ZnO/Al2O3 nanocatalyst used in fuel cell-grade hydrogen production from methanol: Effect of sonication and fuel/nitrate ratio. (17th February 2018) - Shokrani, Reza; Haghighi, Mohammad; Ajamein, Hossein; Abdollahifar, Mozaffar
ABSTRACT: Fuel cell-grade hydrogen production has been studied via steam reforming of methanol (SRM) over a series of CuO/ZnO/Al2 O3 nanocatalysts fabricated by the combustion method. The effect of sonication and urea/nitrate ratio on the characteristics and catalytic properties of the prepared catalysts has been investigated. The synthesized catalysts were characterized by x-ray diffraction (XRD), field emission scanning electron microscope (FESEM), Particle Size Distribution (PSD), energy dispersive x-ray (EDX), Brunauer-Emmett-Teller (BET) and FTIR analyses XRD patterns showed positive influence of urea/nitrate ratio on CuO and ZnO crystallite sizes. The ultrasonic mixing of primary gel compared with conventional mixing led to lower crystallite size. FESEM images showed that the sample mixed by sonication with a urea/nitrate ratio of 1 had more homogeneous morphology with narrow particle size distribution. EDX results proved the presence of all metals on the surface of the nanocatalysts and better consistence between the gel and surface composition of elements in samples prepared by sonication. Catalytic performance showed that sonication during the mixing of primary gel dramatically increased the methanol conversion. It was also proved that increasing the amount of urea led to lower catalytic activity. The ultrasound-treated nanocatalyst with urea/nitrate = 1 was the best sample in terms of activity and selectivity. It was stable in the SRM for 1200 min without considerable change in methanol conversion and product selectivity.